Genetic discrimination: emerging ethical challenges in the context of advancing technology - Chapman, Carolyn Riley (J Law Biosci, 2019)
Genetic testing is becoming more widespread, and its capabilities and predictive power are growing. In this paper, we evaluate the ethical justifications for and strength of the US legal framework that aims to protect patients, research participants, and consumers from genetic discrimination in employment and health insurance settings in the context of advancing genetic technology. The Genetic Information Nondiscrimination Act (GINA) and other laws prohibit genetic and other health-related discrimination in the United States, but these laws have significant limitations, and some provisions are under threat. If accuracy and predictive power increase, specific instances of use of genetic information by employers may indeed become ethically justifiable; however, any changes to laws would need to be adopted cautiously, if at all, given that people have consented to genetic testing with the expectation that there would be no genetic discrimination in employment or health insurance settings. However, if our society values access to healthcare for both the healthy and the sick, we should uphold strict and broad prohibitions against genetic and health-related discrimination in the context of health insurance, including employer-based health insurance. This is an extremely important but often overlooked consideration in the current US debate on healthcare.